2017
DOI: 10.1177/1526602817732952
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Iliac Stenotic Lesions on Blood Flow Patterns Near a Covered Endovascular Reconstruction of the Aortic Bifurcation (CERAB) Stent Configuration

Abstract: Purpose: To investigate the effect of distal stenotic lesions on flow patterns near a covered endovascular reconstruction of the aortic bifurcation (CERAB) configuration used in the treatment of aortoiliac occlusive disease. Method: Laser particle image velocimetry measurements were performed using in vitro models of the aortic bifurcation with and without a CERAB configuration in place. A hemodynamically nonsignificant stenosis (ΔP: 9 mm Hg), a hemodynamically significant (ΔP: 26 mm Hg) stenosis, and a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Early intervention of outflow stenosis might prevent failures as the impact of an outflow stenosis on the local wall shear stress is likely to be more extensive, as was previously demonstrated in an in vitro set-up. 20 Besides of the previous treatment, we could not identity strong predictors for loss of primary patency. The study from the United Kingdom identified the following features to be associated with a need for TLR; TASC D disease (OR=2.45, 95% CI: 1.44; 3.71), severe aortic calcification (OR=2.01, 95% CI: 1.03; 2.20), and presence of tissue loss at baseline (OR=1.43, 95% CI: 1.01;4.63).…”
Section: Discussionmentioning
confidence: 83%
“…Early intervention of outflow stenosis might prevent failures as the impact of an outflow stenosis on the local wall shear stress is likely to be more extensive, as was previously demonstrated in an in vitro set-up. 20 Besides of the previous treatment, we could not identity strong predictors for loss of primary patency. The study from the United Kingdom identified the following features to be associated with a need for TLR; TASC D disease (OR=2.45, 95% CI: 1.44; 3.71), severe aortic calcification (OR=2.01, 95% CI: 1.03; 2.20), and presence of tissue loss at baseline (OR=1.43, 95% CI: 1.01;4.63).…”
Section: Discussionmentioning
confidence: 83%
“…In another experimental study, it was observed that a hemodynamic significant outflow stenosis is related to a two-fold decrease in peak outflow velocity and a three-fold decrease in time-averaged wall shear stress in both CERAB and control models. 17 In CERAB, however, the time-averaged wall shear stress was two-fold lower compared to the control model, independent of the lesion severity. As a low wall shear stress is related to progression of atherosclerosis, this indicates that outflow stenosis after CERAB may have a higher tendency to progress in time and warrant surveillance and potentially early treatment.…”
Section: Proof Of Conceptmentioning
confidence: 83%
“…The covered endovascular repair of the aortic bifurcation (CERAB) technique, which was first introduced in 2013 by Goverde et al, is believed to be a promising technique for extensive AIOD. 11,[28][29][30][31] The new technique uses three balloon-expandable covered stents to create an aortic neobifurcation. It was reported to be able to offer superior flow geometry, additional physiologic flow patterns in vitro, and superior 3-year patency rates and clinical improvements in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported to be able to offer superior flow geometry, additional physiologic flow patterns in vitro, and superior 3-year patency rates and clinical improvements in vivo. 11,[29][30][31] However, the devices are not commercially applied in our institution. As a result, the kissing stent technique with bare-metal stents or covered stent grafts was performed in 9 (52.9%) patients in this study.…”
Section: Discussionmentioning
confidence: 99%